Pastoralism in Urdu Poetry - Dr. Aurangzaib Niazi (Zaban-o-Adab, 2022)
Pastoral is a broader literary term. It encompasses idyllic, georgic and all other types of literary genres which express the simplicity of villages life, wilderness and sheer beauty of nature. In its essence, Pastoral defines the relationship between literature and natural world. While the western literature has a rich tradition of pastoral (is heavily laden with textures),Urdu literature does not have any proper tradition of pastoral except the rare glimpses of pastoral seen in Urdu poetry throughout the era from classic to modern poem. This article aims to high light the colors of Pastoral in selected modern Urdu poetry.